The attenuation in the speech of Havana: Sociopragmatic patterns according to the PRESEEA corpus - Gou, Jialing (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
In the last decade, the solid theoretical, conceptual, and methodological systematization developed by the PRESEEA_ATTENUATION, stimulate the increase of the variationist study of attenuation as a sociopragmatic phenomenon. Currently, there is research with high scientific rigor on the operation of attenuation in various Spanish-speaking communities. However, in Cuba, the examination of the attenuation is practically nil, very little progress has been made in the knowledge of its use in the speech of this Caribbean country. For this reason, this study is carried out with the aim of sociopragmatically characterizing the use of attenuation in the PRESEEA - Havana corpus.